Glypican-3 is expressed in rhabdomyosarcomas but not adult spindle cell and pleomorphic sarcomas. Issue 7 (14th April 2011) - Thway, Khin; Selfe, Joanna; Missiaglia, Edoardo; Fisher, Cyril; Shipley, Janet
Abstract : Aims: Glypican-3 (GPC3) is a membrane-bound heparan sulphate proteoglycan. Glypicans are predominantly expressed during development in cell- and tissue-specific manners and act as co-receptors for many heparin-binding growth factors, playing important roles in cell growth and differentiation. GPC3 expression has been linked to several visceral malignancies, but its role in sarcomas is unexplored. Rhabdomyosarcomas (RMS), the most common paediatric soft tissue sarcomas (STS), are aggressive tumours that frequently show histological overlap with other STS. Immunohistochemistry was performed on tissue microarrays to study GPC3 expression in paediatric RMS and a variety of the more common spindle cell and pleomorphic adult sarcomas. Methods: 642 tumour samples encompassing alveolar and embryonal RMS and adult STS (fibrosarcoma, synovial sarcoma, leiomyosarcoma and undifferentiated pleomorphic sarcoma) were stained with anti- GPC3, and percentage expression in tumour cells was scored on a scale of 0 to +3. Results: GPC3 immunostaining was positive (+1 to +3 expression) in 34.7% (74/213) of RMS samples (15/60 alveolar, 54/143 embryonal, 5 RMS not otherwise specified), but negative or negligible in all other sarcoma samples. Conclusions: This is the first study of GPC3 in a large series of sarcomas, and highlights expression of GPC3 in RMS but not other STS. As glypicans are rarely expressed in mature tissue, GPC3 may be a therapeutic target in RMS, and as the protein can be shed from the cell surface, it may have future application as a biomarker for this disease.